Lanthanide-based luminescent NanoGUMBOS - Dumke, Jonathan C (Langmuir : the ACS journal of surfaces and colloids, 2010)
Lanthanide photochemistry has been frequently studied for its high luminescence intensity, narrow emission band, and stable luminescent lifetime decay. In the work presented here, nanoparticles prepared using an aerosolization process were derived from europium-based GUMBOS (Group of Uniform Material Based on Organic Salts). These nanoparticles were characterized using electron microscopy, X-ray photoelectron spectroscopy (XPS), absorbance, and photoluminescence spectroscopy. An average diameter of 39.5 ± 8.4 nm for our nanoparticles was estimated by use of electron microscopy. Absorbance, luminescence, and luminescence lifetime decay measurements indicate intense and steady luminescence, which suggests a multitude of possible applications for lanthanide-based GUMBOS, especially in sensory devices, OLEDs, and photovoltaic devices